Causes of stress and poor wellbeing among paramedic students in Saudi Arabia and the United Kingdom: a cross-cultural qualitative study - Adnan Alzahrani; Chris Keyworth; Caitlin Wilson; Judith Johnson (BMC, 2023)
Abstract Background Paramedicine presents students with numerous challenges, including factors threatening their wellbeing. Over the last two decades studies have illustrated that paramedics and paramedic students are more likely to have mental disorders than the general population. These findings suggest that course-related factors could be important in contributing to poorer mental health. However, few studies have examined factors related to stress in paramedic students, and none of these have included paramedic students from cross-culture. To address this, the present study (1) explored paramedicine students' training experiences and other education-related factors that could affect their wellbeing, and (2) illustrated the possible differences and similarities between two cultures (Saudi Arabia and the UK) to determine whether the students' cultural environment influenced factors related to their wellbeing. Methods A qualitative exploratory research design was used. Twenty semi-structured interviews were conducted with paramedicine students from the United Kingdom and Kingdom of Saudi Arabia (ten participants from each country). Reflexive thematic analysis was employed as the analytical approach in this study. Results Four major themes were identified which captured the contributors to paramedic students' stress levels: (1) exposure to potentially traumatic events, (2) relationships and communication, illustrating the student's personal and professional experiences with others, (3) programme atmosphere, demonstrating the challenges and support students encounter during their coursework and training, and (4) career, elucidating the pressure of future career expectations and predictions. Conclusion The study revealed contributors to stress were similar in both countries. Better preparation can help to reduce the negative impacts of the possible traumatic events encountered on placements and supportive relationships, especially with proctors, can boost student wellbeing. Universities are able to address both these factors and help foster a positive environment for paramedicine students. As such, these results should help educators and policymakers when identifying and delivering interventions to support paramedic students.